Immune cell networking in solid tumors: focus on macrophages and neutrophils - Di Ceglie, Irene; Carnevale, Silvia; Rigatelli, Anna; Grieco, Giovanna; Molisso, Piera; Jaillon, Sebastien (Frontiers in Immunology, 2024)
The tumor microenvironment is composed of tumor cells, stromal cells and leukocytes, including innate and adaptive immune cells, and represents an ecological niche that regulates tumor development and progression. In general, inflammatory cells are considered to contribute to tumor progression through various mechanisms, including the formation of an immunosuppressive microenvironment. Macrophages and neutrophils are important components of the tumor microenvironment and can act as a double-edged sword, promoting or inhibiting the development of the tumor. Targeting of the immune system is emerging as an important therapeutic strategy for cancer patients. However, the efficacy of the various immunotherapies available is still limited. Given the crucial importance of the crosstalk between macrophages and neutrophils and other immune cells in the formation of the anti-tumor immune response, targeting these interactions may represent a promising therapeutic approach against cancer. Here we will review the current knowledge of the role played by macrophages and neutrophils in cancer, focusing on their interaction with other immune cells.